HUBUNGAN MUTU PELAYANAN KEPERAWATAN DENGAN KEPUASAN PASIEN YANG DIRAWAT DI RUANG RAWAT INAP PUSKESMAS MUMBULSARI JEMBER - Irwin Santoni; Said Mardjanto (Jurnal Kesehatan dr. Soebandi, 2016)
The quality of nursing services is the result of the performance displayed by the nurse. The quality of nurse services is very important in increasing patient satisfaction by itself will foster the image of Puskesmas. The quality of nursing services provided will cause a reaction to the results of the services provided, if the services provided are in accordance with the wishes / desires of the patient it will lead to customer satisfaction. The purpose of this study was to determine the relationship between the quality of nursing services with the satisfaction of patients treated in the Mumbulsari Public Health Center in Jember. This type of research uses the type of correlation research. The population is inpatients at Mumbulsari Public Health Center in Jember and has certain characteristics totaling 45 people. The sample consisted of 40 people with sampling using purposive sampling technique. Methods of data collection using the SERVQUAL scale questionnaire then the data were analyzed using the chi square statistical test with the results of p value = 0.02 <α = 0.05. The conclusion in this study is that there is a relationship between the quality of nursing services with the satisfaction of patients treated in the Mumbulsari Public Health Center in Jember. The existence of a significant relationship between the quality of nursing services with significant patient satisfaction certainly shows that the services provided are in line with customer expectations / desires it will lead to customer satisfaction, but vice versa if the services provided are not in line with customer expectations / desires it will lead to customer dissatisfaction or customer complain